2011
DOI: 10.3310/hta15240
|View full text |Cite
|
Sign up to set email alerts
|

Conservative treatment for urinary incontinence in Men After Prostate Surgery (MAPS): two parallel randomised controlled trials

Abstract: An electronic version of this title, in Adobe Acrobat format, is available for downloading free of charge for personal use from the HTA website (www.hta.ac.uk). A fully searchable DVD is also available (see below).Printed copies of HTA journal series issues cost £20 each (post and packing free in the UK) to both public and private sector purchasers from our despatch agents.Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per issue and for the rest of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 47 publications
(42 reference statements)
0
68
0
6
Order By: Relevance
“…They were grouped into two categories: PFMT versus controls [20,21,22,23] and PFMT at home versus PFMT guided by a physiotherapist [4,24,25,26]. Four studies [20,21,22,23] compared performing PFMT exercises with a control group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They were grouped into two categories: PFMT versus controls [20,21,22,23] and PFMT at home versus PFMT guided by a physiotherapist [4,24,25,26]. Four studies [20,21,22,23] compared performing PFMT exercises with a control group.…”
Section: Resultsmentioning
confidence: 99%
“…Improvements in anatomical knowledge and surgical techniques have considerably reduced morbidity after radical prostatectomy [3]. Nevertheless, many patients suffer from moderate to severe urinary incontinence (UI) after surgery [4]. UI is defined by the International Continence Society as any involuntary loss of urine [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of studies which used PFM exercises are shown in Table 1a;1b;1c;1d and those which used PFM exercisesin combination with electric stimulation for treatingpost-prostatectomy UI are shown in Table 2a;2b;2c. We excluded studies by Manassero et al (13) because their treatment consisted in prescribed exercises to be done only at home; Glazener et al (14) to presenting a heterogeneous sample group of postprostatectomy patients; Glazener et al (15) and Dorey et al (16) for not presenting the results described in the study; Centemero et al (17) …”
Section: Resultsmentioning
confidence: 99%
“…Die BP kann bei prostatogen bedingtem Nachtröpfeln [51,52], nach TUR-P [53] oder nach radikaler Prostatektomie [54] zur Verbesserung der Belastungsinkontinenz führen.…”
Section: Therapieoptionen Der Belastungsinkontinenz Beckenbodenphysiounclassified